Structural organization of normally located mitral valve chordae tendineae of the human heart. - Fedonyuk, L. Ya.; Malyk, Yu. Yu. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. The mitral valve complex of the human heart consists of: the fibrous annulus, valve leaflets, chordae tendineae and papillary muscles. Deficiency or degeneration one of these structures may result in the dysfunction of the valvular apparatus. Topography and structure of the chordae tendineae effect to the normal functioning of heart valve complex and its hemodynamics, due to the aim of our research was to examine the peculiarities of the structural organization normally located mitral valve chordae tendineae of the human heart. Methods. The investigation was made on sectional material. We used light microscopy and immunohistochemistry methods. Results. The chordae tendineae are cord-like tendons that connect the papillary muscles to the valve leaflets in the heart. The chordeae tendineae were covered by endocardium which contained superficial layer of endothelium. Subendocardial layer includes loosely located collagen and elastic fibers which were interwoven with each other. Cor of the chordae are composed of bundles of densely packed collagen fibrils with few elastic fibers. Conclusion. The investigations allowed to receive a new objective data on some structural peculiarities of chordae tendineae of the human mitral valve that later can become the basis for the differential diagnosis of disease, including valvular heart pathology.